220k views
0 votes
If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the first equation is substituted into the second equation.

x + 4y = −9
2x + 5y = −6

A. 2x + 5(4y − 9) = −6
B. 2x + 5(−4y − 9) = −6
C. 2(4y − 9) + 5y = −6
D. 2(−4y − 9) + 5y = −6

User Ezaquarii
by
5.1k points

1 Answer

2 votes
The answer would be D.
The only you thing you have to do is alter the first equation to isolate the x. You do that by moving the 4y to the other side, giving you:
x=(-4y-9)
Then you simply insert your new value for x into the second equation.
Hope this helps. :)
User RetnuH
by
5.3k points